Teacher Professional Development: The Story of English Teacher's Beliefs and Practices - Septhina Shinta Sari; Joko Nurkamto; Dewi Rochsantiningsih (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
Teacher professional development is often seen as the key to powerful education improvement. Therefore, teachers are expected to experience continuous professional development to keep abreast with the endless change taking place in the education routines. This study revealed the teacher’s beliefs and practices regarding with teacher professional development activities. Using qualitative study, mainly through written guided reflection and interview, this investigation resulted in two important findings. The first dealt with the teacher’s strong and positive beliefs toward teacher professional development activities and the other revealed the teacher’s exemplary practices. Hence, this research gives the implication for the teachers to always be involved in life-long endeavor to maintain the professionalism.